The Epic of Manas as a phenomenon of human memory in the treasury of peoples thought (Journal of Philosophy Culture and Political Science, 2018)
The Epic of Manas became a monument of spiritual culture of the Kyrgyz people due to the phenomenon ofhuman memory. Many scientifi c minds since ancient philosophers to modern intellectuals have been interested inthe memory phenomenon. But the main feature is that memory contributes to preservation and augmentation oforal folk arts’ achievements. Memory, as a special form of transmission, has preserved the great achievement ofthe Kyrgyz people – the Epic of Manas. And today, in the age of globalization, Kyrgyz epic is included in the listof Masterpieces of the Cultural Heritage of Mankind.Key words: memory, epic, monument, culture, the thinker, cognition, oral folk arts, culturalheritage, succession.